Implementación de un aplicativo móvil de transaccionalidad para la cooperativa Innovación Andina Ltda., aplicando una metodología de desarrollo de software Scrum. - Plaza Rodríguez, María del Carmen (2022)
The Savings and Credit Cooperative Innovation Andina Ltda, has about 890 members who daily make deposits, withdrawals, transfers and payment of basic services, for which they must physically go to the cooperative windows, this implies that they waste time in mobilization, have to make long lines, transfer cash susceptible to loss or theft, which is why the development of a mobile application that allows systematizing these processes is proposed. For the development of the application, research methods such as the Hypothetical - Deductive method were used to generate the hypothesis and then generate the problem statement, the Deductive method allowed to establish the conclusions, the research techniques were also used, which were very useful to collect the requirements such as field observation, interview and survey, as research instruments the field diary and the questionnaire, in addition the Scrum methodology was used which follows a set of steps for the development of applications in an easy and efficient way and that meets user requirements. As development tools, the Android Studio development environment was used, it is totally focused on Android programming, the Java programming language is widely used by programmers, it allows the design of applications that can be executed on different platforms and the XML design language which allows defining a set of rules to encode documents is characterized by its ease of use and simplicity of web services, these development tools allowed to obtain a secure and fast application.